2017
DOI: 10.1111/ggi.13077
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection in patients with hip fracture: An underestimated event?

Abstract: Patients with UTI seem to be at risk of inferior functional outcomes. In addition to an early detection of symptomatic UTI and a targeted antibiotic therapy, perioperative care should focus on preserving functional ability to protect these patients from further loss of independence and prolonged clinical courses. Geriatr Gerontol Int 2017; 17: 2369-2376.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 34 publications
4
33
0
1
Order By: Relevance
“…In addition to increasing the risk for CAUTI, indwelling catheters are associated with local trauma to the urinary meatus, restriction of mobility, pain, encrustation, delirium and increased risk of mortality. A recent study by Bliemel et al, (2017) of 402 surgically-treated older hip fracture patients concluded that those who developed a CAUTI seemed to be at risk of inferior functional outcomes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition to increasing the risk for CAUTI, indwelling catheters are associated with local trauma to the urinary meatus, restriction of mobility, pain, encrustation, delirium and increased risk of mortality. A recent study by Bliemel et al, (2017) of 402 surgically-treated older hip fracture patients concluded that those who developed a CAUTI seemed to be at risk of inferior functional outcomes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The occurrence of NIs (most frequently—UTI) further worsened the ADL disability in their study. In other study, patients with UTI seemed to be at risk of inferior functional outcomes also in the case of older people after hip fracture [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, such patients depend on immediate full-weightbearing. In this context, several studies on geriatric trauma patients have shown that postoperative early full-weightbearing mobilization significantly reduces perioperative complications and mortality [10,11]. Modern polyaxially angular stable plates offer a crucial advantage in terms of stability and, therefore, in the treatment of geriatric trauma patients with distal femoral fractures [12][13][14].…”
Section: Discussionmentioning
confidence: 99%